Bicyclists and other things that go fast must overcome air resistance, or drag, even to maintain a constant speed. A simple empirical model for the drag force on an object when the air flows smoothly around the object is F D r a g = − c v , where v is the velocity of the object and c is a constant that depends on the size and shape of the object. Consider a bicyclist putting out some power P 0 (in watts) to overcome drag and maintain some constant speed v 0 . She then increases her speed to 1 . 2 v 0 , which requires her to put out a power P 1 to maintain. What is the ratio P 0 P 1 ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We will use the formula P = Δ t W = Δ t F x = F ( Δ t x ) = F v
When the bicyclist travels at speed v , the drag force is − c v , so he needs to exert a force F = c v to travel at constant speed. Thus, P = F v = c v 2
Thus the power is directly proportional to the square of the speed. When the speed increases by 1 . 2 times, the power increases by 1 . 2 2 = 1 . 4 4 times. Therefore P 0 P 1 = 1 . 4 4 .
The general equation for Power is d t d W = d t d ( F × x ) = d t d F × x + d t d x × F , where F is the force and x is the displacement. The phrasing of the problem implies d t d F will be 0 , because the problem asks for the power needed to maintain the new speed 1 . 2 v , and taking the derivative of F which will be dependent on a constant speed will be 0 .
So, the Power at any speed will be F × d t d x = F × v = − c v 2 . Plugging in 1 . 2 v and v and dividing, we get 1 . 4 4
It's a lot easier without calculus. Given P 0 = − c v 0 2 and P 1 = − c ( 1 . 2 v 0 ) 2 , it follows that P 0 P 1 = 1 . 4 4 .
nice
Power=Work/time.
Since Work=Force × distance, Power=Force × distance/time.
Since distance/time=speed, Power=Force × speed.
F 0 = − c v 0 , so P 0 = F 0 v 0 = − c v 0 2 .
F 1 = − c v 1 , so P 1 = F 1 v 1 = − c v 1 2 = − c ( 1 . 2 v 0 ) 2 .
P 1 / P 0 = 1 . 4 4 .
F d r a g = − c v
P d r a g = F v = − c v 2
when P amount of power is applied , velocity increases and hence drag force also increases until P a p p l i e d = − P d r a g
P a p p l i e d = − ( − c v 2 )
P a p p l i e d = c v 2
Hence, P a p p l i e d is directly proportional to v 2
P 0 P 1 = v 0 2 ( 1 . 2 v 0 ) 2
P 0 P 1 = 1 . 4 4
Problem Loading...
Note Loading...
Set Loading...
We note that power is simply energy exerted over time. Since the formula for kinetic energy is K E = 2 1 m v 2 , we know that energy required in creating the force to counter drag is proportional to the square of the velocity of the object. Since the drag force is directly proportional to the velocity of the object, and the power is proportional to the force output, we have that the new power ratio is simply 1 . 2 2 = 1 . 4 4 .